Modern recording techniques - Huber, David Miles (Focal Press, 2014)
Modern Recording Techniques 8th Master the tools and day-to-day practices of music recording and production. Learn the ins and outs of room acoustics and designing a studio. Gain techniques for mic placement and running a session. Get a solid grounding in both theory and industry practice. Modern Recording Techniques , the bestselling, authoritative guide to recording, provides everything you need to improve your craft. "If you're serious about recording--whether you're an amateur enthusiast, a student, a musician, or an audio professional, you'll find this book an informative, in-depth, cover-to-cover read and a useful reference manual...an excellent read and a must-have reference book." - MusicTech magazine Expanded to include the latest digital audio technology, the eighth edition now has sections on touch technology, tablets, and newer connectivity options, such as Thunderbolt. It also includes revamped graphics throughout, and major updates of the sections covering DAWs, MIDI, and mastering. Whether you are just starting out or are looking for a step-up in the industry, Modern Recording Techniques provides an in-depth read on recording; it is a must-have for your audio bookshelf.